Numerical Investigation of Sheet-Gyroid Structure Modifications for Mixing Application in Renewable Energy Technologies - Martin Beer; Radim Rybár (Energies)
The presented study focuses on evaluating the mixing properties of structures derived from the so-called sheet-gyroid geometry and their modifications as advanced mixing elements in renewable energy technologies. Using numerical simulations based on computational fluid dynamics (CFD), the hydrodynamic characteristics of the basic sheet-gyroid structure and five geometric modifications were analyzed under laminar flow conditions simulating the mixing of water and ethylene glycol. The evaluation was conducted using the parameters mixing index and performance index, which express the efficiency of fluid homogenization and its associated energy demands. The results show that all tested geometries significantly improve the degree of mixing compared to an empty channel. The highest concentration homogeneity and best energy efficiency were achieved by the twisted sheet-gyroid structure. This geometric modification exhibits the highest value of the performance index, confirming its ability to achieve excellent mixing with minimal pressure losses. The results of the study demonstrated that, despite similar hydraulic losses among some of the structures, their fluid mixing performance differs, which highlights the importance of targeted geometric design of sheet-gyroid structures. These findings are essential for the design of efficient mixers in technological applications where intensive mixing combined with minimal energy consumption is a critical factor.